Flowcheck: A Discrete Flow Matching Approach for Generating Chess Configurations - Melício, Vinícius do Carmo; Cuba, Manolo Canales; Santos, Charles Morphy D.; Gois, João Paulo (Anais da Conference on Graphics, Patterns and Images (SIBGRAPI), 2025)
We introduce FlowCheck, a novel method for generating realistic chess positions by treating the board as a discrete grid. Our approach uses Discrete Flow Matching (DFM) to train a Vision-Transformer-based model that generates board states conditioned on high-level strategic labels, such as material balance and engine score. A key innovation is the ability to create positions based on specific tactical concepts and a post-processing heuristic to refine the outputs for greater accuracy. FlowCheck produces configurations with a repetition rate of less than 0.02%, and our refinement step significantly improves the fidelity to the desired engine evaluation. This approach offers a powerful tool for procedural content generation, with applications in tailored player training, strategic exploration, and the creation of unique educational content.